2010
DOI: 10.1007/s00127-010-0248-5
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral problems among children living in orphanage facilities of Karachi, Pakistan: comparison of children in an SOS Village with those in conventional orphanages

Abstract: We found a high burden of behavioral problems among children living in orphanages of Karachi, Pakistan. Foster mothers' depression and child's nutritional status, which are associated with behavioral problems, can be target of interventions to reduce behavioral problems of children living in orphanages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
54
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(62 citation statements)
references
References 28 publications
5
54
3
Order By: Relevance
“…The absence of randomised trials restricted any inferences we could draw because of issues related to potential selection bias of children to family-based placements. Although some studies suggested no differences in internalising domains on the basis of placement form, 28,29 most studies suggested greater internalising difficulties in children in institutional care. 3034 All studies that examined externalising psychopathological symptoms showed more difficulties in those children in institutional care compared with children in foster care, 3033 and one study showed only greater behavioural difficulties in girls in institutional care compared with girls in families.…”
Section: Figurementioning
confidence: 95%
See 1 more Smart Citation
“…The absence of randomised trials restricted any inferences we could draw because of issues related to potential selection bias of children to family-based placements. Although some studies suggested no differences in internalising domains on the basis of placement form, 28,29 most studies suggested greater internalising difficulties in children in institutional care. 3034 All studies that examined externalising psychopathological symptoms showed more difficulties in those children in institutional care compared with children in foster care, 3033 and one study showed only greater behavioural difficulties in girls in institutional care compared with girls in families.…”
Section: Figurementioning
confidence: 95%
“…3034 All studies that examined externalising psychopathological symptoms showed more difficulties in those children in institutional care compared with children in foster care, 3033 and one study showed only greater behavioural difficulties in girls in institutional care compared with girls in families. 29 Only one study examined inattention, and showed that boys placed in residential care had more symptoms than boys in foster care. 35 …”
Section: Figurementioning
confidence: 99%
“…If we used those criteria for our data then the rate of behavior problems would be 41.53%. In another study of children living in orphanages the rate was 33% [56]. In our sample trauma had less pronounced effects on the broad psychopathology than on PTSD.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, the other director's response cited providing care and love to children. As Lassie et al (2010) stated, the SOS Children's Villages' philosophy should be applied to other orphanages, because the notion of establishing a family for children who have lost their own biological ones has shown a positive influence on the children.…”
Section: Providing a Nurturing Environmentmentioning
confidence: 99%
“…In addition, the employees need to be passionate and satisfied. Furthermore, they noted the need to establish a family based CC, as advocated by Lassie et al (2010).…”
Section: The Constitution Of Effective Management Of CCmentioning
confidence: 99%